Digital health data security practices among health professionals in low-resource settings: cross-sectional study in Amhara Region, Ethiopia - Ayenew Sisay Gebeyew; Wondwossen Zemene; Binyam Chaklu Tilahun; Nebyu Demeke Mengestie; Berhanu Fikade Endehabtu; Zegeye Regasa Wordofa; Mitiku Kassaw Takillo; Gedefaw Belete Ashagrie; Melaku Molla Sisay (BMC Medical Informatics and Decision Making)
Abstract Introduction Protecting digital health data from unauthorized access, alteration, and destruction is a crucial aspect of healthcare digitalization. Currently, digital security breaches are becoming more common. Healthcare data breaches have compromised over 50 million medical records per year. In Ethiopia, health digitization has grown gradually. However, there is a limitation of study in digital health security. Studying digital health data security helps individuals protect digital data as a baseline and contributes to developing a digital health security policy. Objective To assess the practice of healthcare professionals in digital health data security among specialized teaching referral hospitals in Amhara Region, Ethiopia. Method A cross-sectional study design supplemented by a qualitative purposive sampling method was used to measure the digital data security practices of health professionals. The sample size was determined via single population proportion formula. A simple random sampling technique was used for the study participants. Then, self-administered questionnaires were administered. Multivariable logistic analysis was used to identify associated factors using STATA software. For the qualitative study, key informant interviews were used and analyzed using thematic analysis approach via open-code software. Results Out of the 423 health professionals, 95.0% were involved in the survey. The finding indicates digital health data security practice of health professionals working at specialized teaching hospitals were 45.0%, CI: (40, 50). Health professionals 41–45-year age group (AOR = 0.107), master’s degree (AOR = 2.45), postmaster’s degree (AOR = 3.87), time to visit the internet for more than two hours (AOR = 2.46), basic computer training (AOR = 2.77), training in digital data security (AOR = 2.14), and knowledge (AOR = 1.76) were associated with the practice of digital health data security. For the qualitative study, three teams were prepared. The findings indicate digital health data security can be improved through training, advanced knowledge and working with digital security. Conclusion The practice of digital health data security in specialized teaching hospitals in the Amhara region was inadequate. Therefore, it can be improved through enhancing education status, increasing the time needed to visit the internet, providing computer training, and updating health professionals’ knowledge toward digital health data security.